Organic Carbon Dynamics In Mangrove Sediments Of North Minahasa, Indonesia - Mandagi, Stephanus (Sam Ratulangi University, 2024)
This study aimed to investigate the carbon content in mangrove sediments within the North Minahasa District Marine Conservation Area and to understand the factors affecting organic carbon dynamics. It is revealed that the carbon content is significantly varied. Carbon content ranged from 13.874 to 132.65 Mg C ha-1 across different sampling locations, with an overall stored carbon content estimated at approximately 645.19 Mg C ha-1. Soil density and depth were identified as key factors influencing carbon storage, with thicker soil density associated with higher carbon reserves. These findings highlight the importance of understanding local sediment characteristics for effective blue carbon ecosystem management and conservation strategies. Keywords: carbon, sediment, mangrove, North Minahasa